Rapid detection of Fusarium circinatum propagules on trapped pine beetles. Issue 4 (26th February 2015) - Fourrier, C.; Antoine, S.; Piou, D.; Ioos, R.; Balci, Y.
Summary Pitch canker is a destructive disease of pine caused by the fungus Fusarium circinatum. This taxon is listed as a quarantine fungus for several regional plant protection organizations throughout the world. Whereas long‐distance spread of the disease is made possible through the trade of infected pine seeds, local spread is caused by aerial dispersion or insect transportation of the fungal conidia. Developing a reliable and efficient tool to detect of F. circinatum in insects would be very useful to monitor the local spread of the pathogen. This tool would also provide the means to assess the range of insect species that could serve as potential vector of the fungus. A DNA extraction protocol was optimized and combined with a real‐time PCR test to detect F. circinatum on pine beetles. Using artificially contaminated Ips sexdentatus, it was shown that the test was able to detect down to 10 F. circinatum conidia per individual, and 20 conidia per batch of 10 insects, which is below the lowest inoculum load occurring in nature. With this technique, several batches of up to 10 insects may be analysed simultaneously, with a timescale for analysis reduced to <5 h and without the need for expertise in Fusarium taxonomy. This tool may be useful to monitor potential spread of the pathogen across regions. Using this method, to date, despite F. circinatum foci occurred in Northern Spanish regions across the border in France, the pathogen was not found on I. sexdentatus.